IVIG Effects on Erythrocyte Sedimentation Rate in Children - Farhad Salehzadeh; Ahmadvand Noshin; Sepideh Jahangiri (Hindawi Limited, 2014)
Background. Erythrocyte sedimentation rate (ESR) is a valuable laboratory tool in evaluation of infectious, inflammatory, and malignant diseases. Red blood cells in outside from the body precipitate due to their higher density than the plasma. In this study we discuss the IVIG effect on ESR in different diseases and different ages. Methods and Materials. Fifty patients under 12 years old who had indication to receive IVIG enrolled in this study. Total dose of IVIG was 2 gr/kg (400 mg/kg in five days or 2 gr/kg in single dose). ESR before infusion of IVIG and within 24 hours after administration of the last dose of IVIG was checked. Results. 23 (46%) patients were males and 27 (54%) were females. The mean of ESR before IVIG was 31.8±29.04 and after IVIG it was 47.2±36.9; this difference was meaningful (P=0.05). Results of ESR changes in different age groups, 6 patients less than 28 days, 13 patients from 1 month to 1 year, 20 patients from 1 to 6 years old, and 11 patients from 6 to 12 years have been meaningful (P=0.001, P=0.025, and P=0.006, resp.). Conclusion. In patients who are receiving IVIG as a therapy, ESR increased falsely (noninflammatory rising); therefore use of ESR for monitoring of response to treatment may be unreliable. Although these results do not apply to neonatal group, we suggest that, in patients who received IVIG, interpretation of ESR should be used cautiously on followup.